Effect of Cogranulation on Oxidation of Elemental Sulfur: Theoretical Model and Experimental Validation. Issue 5 (30th August 2016) - Degryse, Fien; da Silva, Rodrigo C.; Baird, Roslyn; McLaughlin, Mike J.
Abstract : Core Ideas: Fertilizers with ES are usually in granular form. Cogranulation of ES reduces its oxidation rate. This granulation effect was modeled based on the reduction in effective surface area. The model was verified against experimental data for ES‐fortified fertilizers. Most studies on elemental sulfur (ES) oxidation have focused on small ES particles mixed through soil, even though commercial ES fertilizers are usually in granular form. Although it has been recognized that cogranulation of ES decreases its oxidation rate, no attempt has been made to quantify this effect. We developed a conceptual model that predicts the "effective diameter" (the diameter of ES particles mixed through soil that would oxidize at the same rate as the granulated ES) by taking into account the effect of granulation on the effective surface area available to the ES in the granule cavity after the soluble macronutrient compound in the fertilizer has diffused away. To validate the model, the oxidation rate was determined for ES‐fortified monoammonium phosphate fertilizer with varying ES content (20–250 g kg −1 ), ES particle diameter (25 or 60 μm), and granule diameter (1.8 or 3.4 mm). The time to reach 50% oxidation varied from 17 d for small granules at the lowest ES content to 210 d for the large granules with the highest ES content. In agreement with the model predictions, reducing ES particle size did not affect the oxidation rate except at the lowest ES rate, whereas reducing granule size increased the oxidation rate. Predicted and observed oxidation rates were in good agreement, indicating that the model describes the effect of granulation with reasonable accuracy. This model may assist in improving formulation of ES‐containing fertilizers and guiding fertilizer recommendations.